Assimilation of Cholesterol by Monascus purpureus - Theresa P. T. Nguyen; Margaret A. Garrahan; Sabrina A. Nance; Catherine E. Seeger; Christian Wong (Journal of Fungi, 2020)
Monascus purpureus, a filamentous fungus known for its fermentation of red yeast rice, produces the metabolite monacolin K used in statin drugs to inhibit cholesterol biosynthesis. In this study, we show that active cultures of M. purpureus CBS 109.07, independent of secondary metabolites, use the mechanism of cholesterol assimilation to lower cholesterol in vitro. We describe collection, extraction, and gas chromatography-flame ionized detection (GC-FID) methods to quantify the levels of cholesterol remaining after incubation of M. purpureus CBS 109.07 with exogenous cholesterol. Our findings demonstrate that active growing M. purpureus CBS 109.07 can assimilate cholesterol, removing 36.38% of cholesterol after 48 h of incubation at 37 °C. The removal of cholesterol by resting or dead M. purpureus CBS 109.07 was not significant, with cholesterol reduction ranging from 2.75–9.27% throughout a 72 h incubation. Cholesterol was also not shown to be catabolized as a carbon source. Resting cultures transferred from buffer to growth media were able to reactivate, and increases in cholesterol assimilation and growth were observed. In growing and resting phases at 24 and 72 h, the production of the mycotoxin citrinin was quantified via high-performance liquid chromatography-ultraviolet (HPLC-UV) and found to be below the limit of detection. The results indicate that M. purpureus CBS 109.07 can reduce cholesterol content in vitro and may have a potential application in probiotics.